A Study on Customer Loyalty, Customer Trust, and Market Orientation Towards Online Business in Saudi Arabia - Liza, U.H. (Institute of Electrical and Electronics Engineers Inc., 2021)
By comparing the change in participants' business knowledge and business acumen to that of traditional corporate training, online business simulations serve as a disruptive technology. Customer loyalty is earned due to the unique nature of services, which increases reliance on technology and customer involvement in service delivery. Customer trust helps to explain why customers are satisfied with their online purchases, where perceived value functions as a partial mediator for relationships with several competitors. As a result, market orientation can either mitigate or amplify the effect of organizational culture on performance outcomes. Unfortunately, there is a paucity of empirical evidence about the mediating impact of market orientation on the organizational culture-performance link. This study aimed to contribute to the body of knowledge regarding online users/customers in the context of online commerce. Additionally, it looks for possible solutions to increase consumer trust, make customers feel secure, and increase customer loyalty to the organization. Following identification, it is necessary to investigate the effects of these elements on internet enterprises. Thus, the purpose of this research is to ascertain the proportion of respondents who utilize the internet and the relationship between customer trust, customer loyalty, and market orientation toward online companies (E-business). Â© 2021 IEEE.